求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 13:54:21
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx求证:1/tanx-tanx=(2cos^2x-1)/s
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx
右式=(cos²x-sin²x)/sinx*cosx
=cosx/sinx-sinx/cosx=1/tanx-tanx=左式
提问数学难题求证:sin^2x*tanx+cos^2x/tanx+2sinx*cosx=tanx+1/tanx
求证tanx-1/tanx=-2/tan2x
求证tanx/2-1/tanx/2=-2/tanx
求证tanx/2-1/(tanx/2)=-2/tanx
求证1+2sinxcosx/cos^2x-sin^2x=1+tanx/1-tanx
求证(1-2sinxcosx)/(cos^2x-sin^2x)=(1-tanx)/(1+tanx)SOS!
求证:(1-2sinxcosx)/(cos^2x-sin^2x)=(1-tanx)/(1+tanx)
1-2sinx cosx /COS^2X-SIN^2X =1-tanx/1+tanx 求证
求证:(1-2sinxcosx)/(tanx-1)=1/(tanx+cotx)-cos^2
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx
求证(1-2sinxcosx)/(cos²x-sin²x)=(1-tanx)/(1+tanx)
(tanx+1/tanx)cos^2 x等于
(tanx+1/tanx)cos^2 x等于
求证tan2/x-1/tanx/2=-2/tanx
求证:(1+secx+tanx)/(1+secx-tanx)=secx+tanx
求证:tanx=sinx√(1+tanx*tanx)
[tanx+(1/tanx)]cos^x
求证:sinX(1+tanX)+cos(1+1/tanX)=1/sinX+1/cosX